Political Regime Theory: Identifying and Defining Three Archetypes - Van den Bosch, Jeroen (The Copernicus Journal of Political Studies, 2018)
This article aims to clear the field of proliferated terminology by clearly defining what constitutes a political regime and what does not. After a clear definition, the article will advocate a dichotomous and trichotomous division for political regimes. Further it will analyze the defining aspects of democratic, authoritarian and totalitarian regimes and draw clear divisions between these archetypes. Finally the paper proposes some well outlined definitions for each regime type. Full text: http://bazhum.muzhp.pl/czasopismo/589/?idno=14760